FRI0461 Muscle wasting in male TNF-α blocker naÏve ankylosing spondylitis patients: a comparison of gender differences in body composition with dual-energy X-ray absorptiometry. (15th June 2017) - Ibáñez, SE Vodnizza; Visman, IM; van, JC Denderen; Lems, WF; Nurmohamed, MT; van, IE der horst-Bruinsma
Abstract : Background: Female Ankylosing Spondylitis (AS) patients have different disease characteristics compared to males. This might be explained by differences in body composition (BC), as women have higher total body fat mass, and adipose tissue can produce adipokines and participate in inflammatory and immunological processes. Objectives: To assess gender differences in BC measured by Dual-Energy X-ray Absorptiometry (DXA) in a cohort of AS patients naïve to TNF-α blockers, and compare the BC with the reference population. Methods: AS patients (Modified New York Criteria), 18 years old or older, who had a whole body DXA analysis before TNF-α blockers were included. Demographic information and disease activity measures (ASDAS and BASDAI) were reported. Fat Mass (FM) was reported as total FM (sum of trunk, arms, legs, and head), BF% (ratio FM/Total body mass), and Fat Mass Index (FMI= FM kg/height m 2 ). Fat Free Mass (FFM), calculated as lean mass + bone mineral content, and its index (FFMI kg/m 2 ) were reported. BF%, FMI, and FFMI percentiles, according to the reference population tables, stratified by age and gender, were also reported. Results: Seventy consecutive patients were included, 60% were men. Baseline demographic characteristics were similar in men and women. Women had significantly higher BF% and FMI, and lower FFMI as absolute values (table 1 ). The FFMI percentile was markedly low in men (31.7%) (Figure 1 ). After multivariate analysis, an ASDAS-CRP >3.5 was related with lower FFM in the whole group (β-coefficient -5.1, 95% CI -10.2 to -0.1, P=0.047). ASDAS >3.5 was related to lower fat content in men and to higher fat content in women. The same relationships were found for BASDAI ≥4. Conclusions: Muscle wasting, measured as low FFMI compared to the reference population, was found in male TNF-α blocker naïve AS patients, especially in those with active disease. Women had higher volumes of body fat than men, but near the median of the reference population. The relationships between fat content and disease activity support the complex association between adipose tissue and inflammation. Acknowledgements: This study was endorsed by an ASAS (Assessment of SpondyloArthritis international Society) Fellowship. Disclosure of Interest: None declared